PENAMBAHAN TEPUNG TULANG CEKER AYAM SEBAGAI SUMBER KALSIUM PADA TAHU KEDELAI - Novidahlia, Noli (Universitas Djuanda, 2010)
The study was done in two stages. The first stages was aimed at making chicken feet bone meal (CFBM) and assessing the nutrient, including water, fat, ash, and calcium) contents of CFBM. A proximate analysis was performed. The second stage was aimed at finding the best organoleptic characteristics (color, taste, aroma, and texture) of CFBM to be used in soya bean tofu. The ratios of CFBM : soya bean tofu were 0.5; 0.75; and 1%.The inclusion of 0.5; 0.75; and 1% CFBM was found to give different organoleptic characteristics of tofu. However, treatment A1 (0.5% CFBM inclusion) was found to give the most preferred tofu. The nutrient contents of CFBM-treated tofu were 8.21% protein, 4.8% fat, 3.5% carbohydrate, and 0.08% calcium.The chosen treatment as a source of calcium was A1 (0.5% CFBM inclusion) as it had the highest score of 4.30 according to panelist’s preference on taste. The nutrient contents of AI-treated tofu were 76.59% water, 2.64% ash, 8.21% protein, 4.80% fat, 3.50% carbocydrate, and 0.08% calcium and the pH was 6.00.